2018
DOI: 10.1038/s41598-017-17214-3
|View full text |Cite|
|
Sign up to set email alerts
|

Pessimism and fearfulness in dairy calves

Abstract: Animals that experience situations likely to induce negative emotions show changes in judgment associated with pessimism. Few studies have focused on whether animals express stable differences in pessimism and whether these differences are related to personality traits. The first aim of this study was to explore if dairy calves are consistent over time in making judgments under ambiguous situations. Our second aim was to determine whether individual differences in judgment bias are related to conventional pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 60 publications
6
69
1
Order By: Relevance
“…Bucking, resting, and withdrawals rarely occurred during the tests and were excluded from further analysis. Behaviors recorded in both novel object and human approach tests were averaged across tests (following Neave et al, 2018a, andLecorps et al, 2018), resulting in 5 behavioral measures (number of vocalizations, latency to touch, and duration of touching, playing, and attentive) and a further 3 behavioral measures for the novel environment test (duration of active, inactive, and exploring). All measures of individual characteristics, feeding behavior, and performance were verified for normality using the PROC UNIVARIATE procedure and probability distribution plots.…”
Section: Discussionmentioning
confidence: 99%
“…Bucking, resting, and withdrawals rarely occurred during the tests and were excluded from further analysis. Behaviors recorded in both novel object and human approach tests were averaged across tests (following Neave et al, 2018a, andLecorps et al, 2018), resulting in 5 behavioral measures (number of vocalizations, latency to touch, and duration of touching, playing, and attentive) and a further 3 behavioral measures for the novel environment test (duration of active, inactive, and exploring). All measures of individual characteristics, feeding behavior, and performance were verified for normality using the PROC UNIVARIATE procedure and probability distribution plots.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the multidimensional character of personality in calves (e.g. [ 22 24 ]) and multiple personality traits have been reported. However, personality traits and their stability might change throughout ontogenesis [ 25 , 26 ] and the contextual and longer-term temporal stability of personality traits in adult lactating cows has rarely been investigated (but see [ 27 , 28 ]).…”
Section: Introductionmentioning
confidence: 99%
“…This problem has become evident for example due to the different interpretations of behaviours expressed in the open field test or in emergence and novel object tests (Beckmann & Biro, 2013;Carter et al, 2013;Perals, Griffin, Bartomeus, & Sol, 2017). Recently therefore, the importance of cross-validating these standardized tests in more ecologically relevant contexts has been recognised, to avoid misinterpretation of behaviours in a context beyond that of the respective test situation (Arvidsson et al, 2017;Lecorps et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They found that the behaviour measured in the standardised test was not correlated with behaviour measured in the semi-natural environment, therefore not measuring the same behaviour. On the other hand, Lecorps et al (2018) found that standardised tests for sociability were related to social proximity in the home pen and tests for fearfulness and pessimism were related to distress experienced during transportation. These examples demonstrate the importance of cross-validating standardised behavioural tests to understand what they are truly measuring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation